Design And Development Of A Backend System For Monitoring And Controlling Smart Agriculture - Febrianti, Maria Shusanti; Marzuki, Marzuki; Agustina, Dian Resha; Prasetyo, Aldi (Yayasan Cita Cendekiawan Al Khwarizmi, 2024)
This study aims to build a system to manage temperature, pH, nutrient, and water availability sensor data for plants in smart agriculture. This is done so that the data sent by the sensor can be managed and stored properly. So that the data can be used for monitoring and controlling later. This study uses a waterfall model. Waterfall is often used to build a software system. The system that has been built needs to be tested. Based on the coding results, the system has two services. The first service handles user data, tools, plants, tool sets, and planting settings. The second service will hold the data that the tool sends to RabbitMQ. The results of the first service test run well, where every request sent by the client can be processed, and a response is returned as a request. In service, in two tests, some services ran fine. Where the data is successfully sent to the client side in real-time; however, when consuming and getting real-time data, it needs to be underlined; if getting real-time data is done when the JSON file is empty, it will return null. This may cause data delays to the client. The monitoring process will be a little late.